Reversal Learning Task in Children with Autism Spectrum Disorder: A Robot-Based Approach. - Costescu, Cristina; Vanderborght, Bram; David, Daniel (Journal of Autism & Developmental Disorders, 2015)
Children with autism spectrum disorder (ASD) engage in highly perseverative and inflexible behaviours. Technological tools, such as robots, received increased attention as social reinforces and/or assisting tools for improving the performance of children with ASD. The aim of our study is to investigate the role of the robotic toy Keepon in a cognitive flexibility task performed by children with ASD and typically developing (TD) children. The number of participants included in this study is 81 children: 40 TD children and 41 children with ASD. Each participant had to go through two conditions: robot interaction and human interaction in which they had performed the reversal learning task. Our primary outcomes are the number of errors from acquisition phase and from reversal phase of the task; as secondary outcomes we have measured attentional engagement and positive affect. The results of this study showed that children with ASD are more engaged in the task and they seem to enjoy more the task when interacting with the robot compared with the interaction with the adult. On the other hand their cognitive flexibility performance is, in general, similar in the robot and the human conditions with the exception of the learning phase where the robot can interfere with the performance. Implication for future research and practice are discussed.